Buyer’s behaviour on gingelly oil - a study with reference to madurai city - M, Sumathy; N, Vijayalakshmi (Journal of Management and Science, 2012)
This study is based on the buyer‟s behaviour towards gingelly oil. A psychometric response scale primarily used in questionnaires to obtain participant‟s preferences or degree of agreement with a statement or set of statements. Likert scales are a non‐comparative scaling technique and are unidimensional (only measure a single trait) in nature. Respondents are asked to indicate their level of agreement with a given statement by way of an ordinal scale.The influence of personal characteristics and buyer‟s preference factors on the behaviour as well as the relationship between buyer and purchasing behaviour of gingelly oil are examined. This study shows that, overall, the consumers have positive attitude towards using of gingelly oil on their daily food.